2023
DOI: 10.1039/d2ta07996h
|View full text |Cite
|
Sign up to set email alerts
|

Dual-purpose tunnel oxide passivated contact on silicon photoelectrodes with high photovoltages for tandem photoelectrochemical devices enabling unassisted water splitting

Abstract: A tandem photoelectrochemical (PEC) water-splitting device for solar hydrogen production consists of two light absorbers with different bandgaps. It is important to enhance the performance of both cells to achieve...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…TTO deposition accounts for the 40 mV difference in photovoltage compared to the value obtained in our earlier study (Pt/Ti/TOPCon Si, 640 mV). [ 10 ] The same structure illuminated with light filtered by a blank BVO (the red curve in Figure S2, Supporting Information) produced an onset potential of 598 mV, which should be the maximum value of photovoltage attainable by TOPCon Si when integrated with BVO. This high photovoltage can be mainly attributed to the insertion of the SiO 2 passivation layer, which decouples the c‐Si absorber from the highly doped poly‐Si charge selective contacts and suppresses Auger‐recombination at the surface of c‐Si.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…TTO deposition accounts for the 40 mV difference in photovoltage compared to the value obtained in our earlier study (Pt/Ti/TOPCon Si, 640 mV). [ 10 ] The same structure illuminated with light filtered by a blank BVO (the red curve in Figure S2, Supporting Information) produced an onset potential of 598 mV, which should be the maximum value of photovoltage attainable by TOPCon Si when integrated with BVO. This high photovoltage can be mainly attributed to the insertion of the SiO 2 passivation layer, which decouples the c‐Si absorber from the highly doped poly‐Si charge selective contacts and suppresses Auger‐recombination at the surface of c‐Si.…”
Section: Resultsmentioning
confidence: 99%
“…[ 11,12 ] The SiO 2 passivating layer also improves the thermal stability by acting as a diffusion barrier, preventing the thermal diffusion of elements from other contacting materials into c‐Si. Our prior study showed the superior thermal stability of TOPCon Si in a temperature range up to 600 °C, [ 10 ] which is sufficient for the high‐temperature processes for SnO 2 and BVO.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moon et al proposed a passivation solution using a tunnel oxide passivated contact (TOPCon) structure. 327 The ultrathin SiO 2 tunnel layer significantly reduces surface carrier recombination rates, while the doped polycrystalline silicon layer forms an ohmic contact between SiO 2 and the metal, resulting in excellent carrier collection efficiency. Additionally, the SiO 2 layer and polycrystalline silicon layer serve as effective diffusion barrier layers and impurity absorption layers, greatly enhancing the thermal stability of the device during high-temperature fabrication processes and preventing the diffusion of metals into Si.…”
Section: Derivative Configurations Of Mis Photoelectrodesmentioning
confidence: 99%